Facial attractiveness: Variation, adaptiveness and consequences of facial preferences - Kościński, Krzysztof (Anthropological Review, 2008)
This review embraces the following topics: intra- and inter-populational variation of facial preferences, relationship between facial attractiveness and mate value, biological and social effects of the perception of facial attractiveness, credibility of the adaptive perspective on facial preferences, and the phylogeny of facial attractiveness. Its main conclusions are as follows: (1) Many sources of inter-individual variation in assessments of facial attractiveness have been identified, e.g., the age, sex, biological quality, physiological state, personality, and living situation of the judge, as well as previously observed faces, physical similarity of the focal face to the judge’s face, and acquaintance with and knowledge of the face owner. (2) Inter-populational consistency in perception of facial attractiveness is substantial and possesses both a biological and a cultural basis. (3) Facial attractiveness is a reliable cue to biological quality of the face owner, e.g., better parasite resistance, physical fitness, reproductive fitness, longevity, less mutational load, higher intelligence and better mental health. (4) Facially attractive people have more sexual partners, marry at a younger age, and remain single less frequently. Thereby, they have higher reproductive success than unattractive individuals. (5) As a whole, research supports the thesis that facial preferences are adaptive, that is, they evolved during the course of biological evolution because they assisted an individual in choosing a mate with good genes or a good personality.